Biogeochemistry of antimony in soil-plant system: Ecotoxicology and human health - Natasha; Shahid, Muhammad; Khalid, Sana; Dumat, Camille; Pierart, Antoine; Niazi, Nabeel Khan (Applied geochemistry, 2019)
Environmental contamination by antimony (Sb), a non-essential and non-beneficial metalloid, is a great threat to living organisms at a global scale. Owing to its various uses in numerous industrial processes, Sb is released into different environmental compartments every year. Environmental Sb contamination can result in food chain bioaccumulation, especially due to its uptake and accumulation in edible plant parts. Consumption of Sb-rich food (cereals, vegetables, pulses etc.) is the key source of Sb exposure to human. Since Sb does not possess any identified biological role and has genotoxic and carcinogenic potential, it is critical to monitor its biogeochemical behavior in the soil-plant system and its influence in term of possible food chain bioaccumulation up to human exposure. However, compared to other heavy metals, limited data is available regarding biogeochemical behavior of Sb in the soil-plant system and associated health risks. This review traces a plausible link among Sb exposure levels, its chemical speciation, and phytoavailability in the soil, uptake/accumulation/compartmentation by plants, phytotoxicity and detoxification inside the plant. The role of different enzymatic (peroxidase, catalase, ascorbate peroxidase, superoxide dismutase, glutathione peroxidase) and non-enzymatic (glutathione, phytochelatins, proline and ascorbic acid) antioxidants have also been elucidated with respect to enhanced generation of reactive radicles and oxidative stress. The review also outlines the role of different transporter proteins in Sb transport/compartmentation inside plants, build-up in edible plant tissues and associated health risks. The biogeochemical role of Sb in the soil and plant systems and associated health risks have been described in 11 tables and 4 figures. [Display omitted] •This review delineates biogeochemical behavior of Sb in soil-plant system.•Biogeochemical behavior of Sb depends on its chemical speciation.•Plants possess an efficient tolerance mechanism to endure Sb bioaccumulation & toxicity.•Sb can cause health risks via food chain contamination.•Less data is available about Sb biogeochemical behavior in soil-plant-human system.